ASPECTS OF TRANSFORMATION OF LOCAL FAMILY PRAYER IN ABKHAZIA - Ajba, Tamara Guramovna (History, Archeology and Ethnography of the Caucasus, 2025)
In the article, the author examines the pastoral rituals that were common in Abkhazia and the North Caucasus. Partially concerns the religious situation in Abkhazia, paying attention to persistent signs of religious syncretism. The author introduces field materials that were collected in the period from 2011-2024, using a longitudinal research method in the work, which made it possible to trace the transformation of the local tribal rite of prayer "Akuabknyhra" - the removal of a copper pot with a wooden lid, presumably once a local shepherd-tribal prayer. Currently, we can observe not so much external changes in the ritual of prayer, although they are definitely present, but its semantic load. If supposedly in the 19th century it was a pastoral rite, the purpose of which was to protect and preserve livestock, now its key significance is to unite a certain kinship group, in the particular case of the Abipara of surname Aiba.Abkhazian Abipara is a patronymic organization, one of the social entities, which is the observance of religious rituals. You can also observe the process of endowing an object with agency: “Akuab” - a copper pot with a wooden lid - becomes a relic, and it is already a kind of icon that is prayed to. There is a shift in emphasis in the patriarchal-tribal system; the role of the priest is assigned to the owner of the house in which “Akuab ” is kept. In this case, this is the youngest son, since in Abkhazia the principles of the minority are predominantly preserved to this day. The transformation of this local ritual of prayer clearly demonstrates how the “old” tradition takes on a different form and gives birth to new narratives.